Propuesta metodológica en la implementación del enfoque itls para la contribución a la calidad y a la mejora continua (2020)
iTLS is a continuous improvement management model proposed by Russ Pirasteuh and Robert Fox in 2010 which, through the application of 7 consecutive steps, integrates the essence of each of the approaches of Theory of Constraints, Lean Manufacturing and Six sigma, proposing a powerful tool focused on quality and improvement of overall performance of the organization allowing proper decision making. Due to the importance of this subject and the need for research on its execution, this article presents the proposal of a detailed and complete methodology that supports the implementation process of the model proposed by Pirasteuh and Fox based on the assumptions that each of the theories integrated therein. This methodology is considered a fundamental tool for the implementation in companies that have little or no experience in the application of the model, proposing an accessible and flexible alternative that leads to the successful practice of the itls model. In addition to covering each of the steps proposed by the authors Pirasteuh and Fox, it also breaks down each of the activities into phases and adds tools that complement this process focused on increasing productivity and quality which would allow for successful continuous improvement at each company level.